Efforts to Improve Student Learning Outcomes Through PowToon Animation Video-Based Learning Media - Sulistiani, Ida (PT Literasi Nusantara Publisher, 2022)
This study aims to develop PowToon video-based learning media on English Language and Literature learning materials. This research uses Classroom Action Research (CAR) procedures. Data were collected through documentation, questionnaire, observation, and test techniques. The data analysis technique used is descriptive quantitative data analysis. In addition to the data from the preliminary study, questionnaire data related to product validity were also analyzed using descriptive analysis. The results of the study indicate that the results of this PowToon-based learning media are valid according to the opinions of experts, are practical in their application, and have a potential effect in increasing students' understanding of learning materials. The increase in student learning outcomes in each cycle from the initial condition of the average daily test score of 66.05 to 78.05 in the final condition, increased by 12.00. So, the recommendation that can be given is that teachers should apply innovative learning models and use learning media. In order to improve learning outcomes, the application of PowToon animation video media should be optimized, so that student learning outcomes are optimal.